Controlling a Car Buggy Using a NIR Camera with Hand Gestures (International Journal of Engineering and Computer Science, 2014)
We live in the digital era where the use of digital components is increasing in automotive engines, direction systems & other devices. Hence giving rise to new user interfaces due increase in Human-Vehicle Interaction (HVI). HVI devices having many key characteristics such as stability, reliability and robustness of the system. HVI devices help to track the gesture, recognize it and perform the desired operations in real time. This can be implemented using hand gesture control mechanism as one of its components. The gestures control technique has become a new trend for many human based electronic products. In this paper we will be using a near infrared Camera (NIR) camera which will track the images which will then be forwarded to the gesture recognition architecture. This architectures makes use of series of different recognition algorithms to recognize the gesture and perform the desired action.